A Dual‐Targeting Circular Aptamer Strategy Enables the Recognition of Different Leukemia Cells with Enhanced Binding Ability. Issue 33 (7th July 2022) - Ai, Lili; Peng, Tianhuan; Li, Yingying; Kuai, Hailan; Sima, Yingyu; Su, Minhui; Wang, Dan; Yang, Qiuxia; Wang, Xue‐Qiang; Tan, Weihong
Abstract: Currently, the broad use of monovalent aptamers in oncology faces challenges, including insufficient recognition and internalization caused by a finite number of receptors on the cell surface, as well as a confined recognition spectrum. Herein, we describe the development of a dual‐targeting circular aptamer (DTCA) that can recognize two different biomarkers on living cells to augment aptamer–receptor interactions, thus enhancing recognition of the target cells. This improvement not only boosts binding and internalization abilities, but also expands the recognition spectrum of these aptamers to different leukemia cells. Moreover, the stability of DTCA in serum can be significantly improved by an enzyme‐promoted terminal ligation strategy. The chemical incorporation of 5‐fluorodeoxyuridine into DTCA resulted in a pharmaceutically functional aptamer that exhibited excellent selectivity, as demonstrated by its high cytotoxicity against target cancer cells, but not to normal cells. The superiority of our newly developed strategy was further highlighted by its precise tumor‐imaging capability. Abstract : To enhance the recognition and internalization ability of aptamers, we designed a dual‐targeting circular aptamer (DTCA) that can simultaneously recognize two different biomarkers on cancer cells to significantly improve aptamer–receptor interactions. This molecular engineering technique considerably boosts binding avidity and expands the recognition spectrum of these aptamers to different subtypes of leukemia cells.